Multi-Group Analysis: Testing Moderating Effects For Causal Structure Model Of Self-Action-Outcome (Sao Model) - Norida, Abdullah; Mohd Shamsuri, Md Saad; Subatira, Balakrishnan; Asiah, Mohd Pilus; Ahmad Tajuddin, Othman (Canadian Center Of Science And Education, 2015)
This study focuses on testing the moderating effects based on gender, academic performance, faculty and residential setting based on Self-Action-Outcome (SAO) model that was developed by the researchers. This model examined the relationship between self-esteem, job-search intensity and career decision-making self-efficacy among undergraduate students. Several instruments were used to develop this model were, the Rosenberg Self-Esteem Scale, Job-Search Intensity Scale, and Career Decision-Making Self-Efficacy Scale. Cluster sampling procedure was used in recruiting the participants. Data were collected using a self-reported questionnaire from 678 undergraduate students and were tested with confirmatory factor analysis to obtain three best-fit measurement models from the three latent variables. The results showed that gender, academic performance, faculty and residential setting did not moderate the hypothesized SAO model which means that the hypothesized SAO model is a good model for undergraduate students. Implications of the findings for social work practice such as guidance counsellor, research, theory, policy and education were also discussed.